The relationship between socially responsible leadership and organisational ethical climate: In search for the role of leader's relational transparency - (:unkn) unknown (Inderscience Publishers, 2019)
This study focused on the interaction between socially responsible leadership, relational transparency and organisational ethical climate. It is assumed that socially responsible leadership has an important role in affecting organisational ethical climate and relational transparency of the leaders also has a role in terms of influencing ethical climate. Thus, it is suggested that perceived relational transparency of the leaders will moderate the relationship between perceived socially responsible leadership and ethical climate. For investigating the hypothesised relationships, a research study was performed on a sample of 246 employees working in Turkish private organisations from different industries including education, banking-finance, tourism and health institutions. A combined questionnaire with five-point Likert scale was used. Results indicated that transparency significantly moderated the relationship between socially responsible leadership and organisational ethical climate. However, the findings of structural equation modelling tests reported that the relation of socially responsible leadership with ethical climate was not significant. Subsequently, further analyses, limitations and future research recommendations are discussed and both academic and practical implications of the study are presented. © 2019 Inderscience Enterprises Ltd.
Keywords: Ethical climate; Governance; Relational transparency; SEM; Socially responsible leadership; SRL; Structural equation modelling